2017
DOI: 10.1007/s00125-017-4264-9
|View full text |Cite
|
Sign up to set email alerts
|

EASL–EASD–EASO clinical practice guidelines for the management of non-alcoholic fatty liver disease in severely obese people: do they lead to over-referral?

Abstract: This is the first study to assess the strategy proposed by the EASL-EASD-EASO clinical practice guidelines for the management of NAFLD in severely obese individuals. The retrospective application of the guidelines in a cohort representing the routine clinical practice in our department would lead to an excessive number of specialist referrals and would also lead to an unjustified increase in health costs. Biomarkers and specific strategy for the screening of NASH and advanced fibrosis in morbidly obese individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 11 publications
2
80
0
3
Order By: Relevance
“…A recent study looking at various combinations of non‐invasive methods found comparable PPV for detecting F3‐F4 . The low PPV indicates the need to develop and use a combination of methods to detect fibrosis and (even more so) cirrhosis that rely on complementary and distinct principles …”
Section: Discussionmentioning
confidence: 99%
“…A recent study looking at various combinations of non‐invasive methods found comparable PPV for detecting F3‐F4 . The low PPV indicates the need to develop and use a combination of methods to detect fibrosis and (even more so) cirrhosis that rely on complementary and distinct principles …”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the reported benefits of the MD components on the features of the MetS, including NAFLD, the MD has been proposed as the diet of choice for the dietary treatment of hepatic steatosis [74]. Herein, we report the current evidence on the liver-related outcomes of the MD diet.…”
Section: Current Evidence About the Effects Of The Mediterranean Dietmentioning
confidence: 97%
“…Interestingly, at a multiple linear-regression age-balanced analysis, the changes in AMDS were related to the reduction in hepatic fat content independently of physical activity. However, a potential limitation of this study is the fact that the BLS is not accurate in the staging of fatty liver and is indeed not included among the validated steatosis scores by the most recent EASL/EASD/EASO guidelines [74].…”
Section: Current Evidence About the Effects Of The Mediterranean Dietmentioning
confidence: 99%
“…A recent study also reports a novel pathway in which hepatic vitamin D receptor (VDR) expression is increased in patients with simple steatosis (nonalcoholic fatty liver without inflammation), and the activated VDR upregulates angiopoietin-like protein 8 (ANGPTL8) expression, thus contributing to triglyceride accumulation in human hepatocytes [115]. At any rate, studies have reported that fibrosis-initiated fatty liver disease progresses over many years, thus providing a potential window for intervention by examining diseaseprogression/modifying factors in NAFLD [116][117][118]. It is important to note that increased BMI and insulin resistance have been associated with a more rapid progression to fibrosis [35,119].…”
Section: The Genetics Of Nafldmentioning
confidence: 99%